PENGARUH PERHATIAN ORANGTUA TERHADAP PRESTASI BELAJAR IPA SISWA DITINJAU DARI MINAT SISWA - Wahyudi Wahyudi; Neng Nenden Mulyaningsih; Popi Purwanti (UNIVERSITAS INDRAPRASTA PGRI, 2020)
This study aims to determine the effect of parental attention on science learning achievement. Knowing the effect of student interest in learning achievement in Science. Knowing the effect of parental attention and student interest in learning together on the science learning achievement of class VII Mts students. Nurul Falah, Areman Depok. The method used in this study is a correlational survey method. The sample in this study was 30 students whose collection was determined based on random sampling techniques. With a description of the data for each variable, the tests carried out are normality and homogeneity tests. In this study, the hypothesis will be tested through statistical methods in the form of regression and correlation tests. Based on the partial regression test, it was obtained tcount <ttable, namely 01.81 <2.052, then H0 was accepted and it was concluded that there was no significant effect of interest in learning (X2) on students' science learning achievement (Y).